Does FDI Drive Economic Growth? Evidence from City Data in China. Issue 11 (1st September 2020) - Wu, Weijun; Yuan, Ling; Wang, Xiaoming; Cao, Xiaping; Zhou, Sili
ABSTRACT: Foreign Direct Investment (FDI) and government spending are two important drivers of economic growth. We use Chinese city level data and document an inverse U shape relation between FDI and GDP growth. FDI's diminishing growth effect becomes more salient for cities with greater budget deficit or relying heavily on local corporate tax. When foreign firms account for sizable share of local capital formation in the economy, FDI significantly crowds out public spending. We attribute the inverse U shape of FDI and growth to both tax distortion and crowd-out effect.